Pengaruh audit delay dan ukuran KAP terhadap audit switching: Kajian dari sudut pandang klien - Arum Ardianingsih (LPPM Universitas Pekalongan, 2014)
Development of business is rapidly increasing influence the development of public accounting profession which affects more Public Accounting Firm (KAP) operating. Number KAP provides many options for companies to keep using the same KAP KAP or make the turn (auditor switching). This study aims to provide empirical evidence of the effect of audit delay and the size of KAP to audit switching. This study uses two variables independence of consist that audit delay and the size of KAP are supposed to influence the audit switching. Testing performed using logistic regression. Test results obtained evidence that audit delay and the size of KAP does not significantly influence the audit switching. Keywords: Audit Delay, The size of KAP and Audit Switching.